Disrupting Hostile Speech on Social Media: Indigenous Fishers and Allies Push Back for Ecojustice - Stan Goto (Adult Education Research Conference, 2019)
This project considers challenges and opportunities for educators to disrupt hostile exchanges on social media concerning environmental sustainability and cultural practice. Postcolonial theory is used analyze fishing-related conversations.
Keywords: ecojustice; sustainability; Indigenous studies; digital literacies